The Lighten up (Lip) gene of Drosophila melanogaster, a modifier of retroelement expression, position effect variegation and white locus insertion alleles. - Csink, A.K.; Linsk, R.; Birchler, J.A. (Genetics, 1994)
We are interested in identifying single gene mutations that are involved in trans-acting dosage regulation in order to understand further the role of such genes in aneuploid syndromes, various types of dosage compensation as well as in regulatory mechanisms. The Lighten up (Lip) gene in Drosophila melanogaster was identified in a mutagenic screen to detect dominant second site modifiers of white-blood (wbl), a retrotransposon induced allele of the white eye color locus. Lip specifically enhances the phenotype of wbl as well as a subset of other retroelement insertion alleles of white, including the copia-induced allele, white-apricot (wa), and six alleles caused by insertion of I elements. We isolated six alleles of Lip which are all recessive lethal, although phenotypically additive heteroallelic escapers were recovered in some combinations. Lip also suppresses position effect variegation, indicating that it may have a role in chromatin configuration. Additionally, Lip modifies the total transcript abundance of both the blood and copia retrotransposons, having an inverse effect on the steady state level of blood transcripts, while showing a non-additive effect on copia RNA.